French Energy Transformation under the Russia-Ukraine Conflict and Reflections on China-France Energy Cooperation in the Future - Yong, Chengyu (International Journal of Electric Power and Energy Studies, 2024)
Since the beginning of the 21st century, France has increasingly prioritized climate change as a central focus of its energy transition strategy. In the wake of the Russia-Ukraine conflict, EU countries are now grappling with a new energy crisis. As one of the major powers within the European Union, France has been continuously adapting and refining its energy transition policies in response to these shifting energy dynamics. This paper examines the various factors contributing to the current energy crisis and analyzes France’s strategies and directions for energy adjustment. It also explores the future prospects of energy cooperation between China and France, particularly in the area of renewable energy. Building on this analysis and drawing parallels with China’s own energy transformation path, the paper offers insights and suggestions that may serve as a reference for China’s future energy transition efforts.